Effect of different doses of sodium azide (NaN3) on some phenological, morphological and production characteristics of three types of soybean Glycine max(L.)merr - زربا, يارا; محمد خطاب; يوسف محمد (Latakia University Journal -Biological Sciences Series, 2023)
The seeds of three Glycine max soybean genotypes (Sb 239, Sb 337, Sb 44) obtained from the Agricultural Scientific Research Authority in Damascus were subjected to mutagenization using the chemical mutagenic sodium NaN3 at concentrations (0 - mM 0.5 - mM 1.0 - mM 1.5 - mM). 2.0 - mM 3 - mM 4), in order to determine the optimum concentration of sodium azide doses and its effect on some phenological, morphological and production characteristics of soybean crop, in order to reach new varieties with high productivity and early flowering and maturity for use in subsequent breeding programs. The mutated seeds were sown in the permanent land in the Damsarkho area within the city of Lattakia during the agricultural season 2021-2022. The results obtained indicated the presence of novel mutations that affected many agricultural traits, and that the chemical mutagen sodium azide was effective in causing mutations in soybeans, with different studied genotypes in their responses to different concentrations of the mutagen, and the concentration mM2. Productivity and primroses, where the largest number of pods and primroses in flowering were reached in all studied models. The Sb337 model was also distinguished by many characteristics, especially the percentage of dead and surviving plants and the length of the roots of seedlings, while the Sb239 model was distinguished by the number of pods in the plant and the first fruits, so we recommend using it as a raw material in the subsequent breeding work for its productive and firstborn traits.